Method for producing water-absorbent resin composition

By using a rotary dryer in the drying process of the water-absorbing resin composition, the problems of uneven drying and deterioration in the prior art are solved, and a more efficient and uniform drying process is achieved, and environmental load and performance deterioration are reduced. .

CN119403863APending Publication Date: 2025-02-07NANTONG JIANGTIAN CHEM CO LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202380051664.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-07
Filing Date
2023-01-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The conventional drying method of water-absorbent resin compositions has problems such as uneven drying, undried substances, increased equipment load, decreased yield, and absorption performance and colored foreign matter.

Method used

The rotary dryer is used to dry, and the aqueous gel is stirred and dried by rotating the rotary cylinder and stirring rod to improve drying efficiency and uniformity.

Benefits of technology

The drying process time is reduced, the environmental load is reduced, the performance deterioration and the generation of colored foreign matter are reduced, and the quality of the water-absorbing resin composition is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403863A_ABST
    Figure CN119403863A_ABST
Patent Text Reader

Abstract

The present invention is a method for producing a water-absorbent resin composition, the method comprising: a polymerization step in which a water-containing gel containing a crosslinked polymer (A) is obtained; and a drying step in which the water-containing gel is dried by a drying machine, the drying machine being a rotary drying machine which has a rotary drum that can rotate about an axis and a rotatable stirring shaft that is disposed in the axis direction and has a stirring rod, and which performs a drying process in the rotary drum. And a drying step for drying the water-containing gel while stirring up the water-containing gel in the rotating cylinder of the rotary dryer by rotating the rotating cylinder and the stirring rod. According to the present invention, it is possible to provide a method for producing a water-absorbent resin composition, which can contribute to a reduction in environmental burden by reducing the time taken in a drying step, and which can reduce the deterioration in performance and the generation of colored foreign matter caused by the drying step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a water-absorbent resin composition. Background Art

[0002] At present, water-absorbent resin compositions made of hydrophilic fibers such as pulp and acrylic acid (salt) as main raw materials are widely used as absorbents in sanitary materials such as disposable diapers, sanitary napkins, and incontinence pads. In recent years, the demand for these sanitary materials has increased worldwide, and in order to meet this demand, it is necessary to improve productivity. In the manufacturing process of the water-absorbent resin composition, it is necessary to dry a large amount of water contained in the water-absorbent resin composition. This drying process becomes a rate-limiting stage, making it difficult to improve productivity.

[0003] In order to speed up the drying speed of the water-absorbent resin composition, there is a method of increasing the drying temperature. However, if the drying temperature is increased, the water absorption performance decreases and the soluble components increase due to the thermal degradation of the highly absorbent resin composition. If the water absorption performance decreases, it is difficult to dry the surface of the sanitary material in contact with the skin, which becomes a cause of rashes. In addition, even if the soluble components increase, it will also become a cause of rashes during the use of the sanitary material. Therefore, it is required to improve the drying method for producing a water-absorbent resin composition with less performance degradation.

[0004] As a method for drying a water-absorbent resin composition, the following methods are conventionally known: a method in which an aqueous solution of an acrylic acid salt is polymerized, the resulting hydrogel is shredded with a chopper, and then dried with a conveyor-type dryer; a method in which an aqueous solution of an acrylic acid salt is polymerized, the resulting hydrogel is neutralized and shredded with a chopper, and then dried with a conveyor-type dryer; Figure 3 A method of drying using a conveyor-type dryer as exemplified in (for example, Patent Document 1 and Patent Document 2).

[0005] However, the conveyor-type static drying requires the drying of the water-containing gel by stacking, which is prone to uneven drying, resulting in the generation of undried matter, and the problems of increased equipment load and reduced yield in the crushing step and classification step as the steps after drying. Therefore, when the water-absorbent resin composition is produced by a conveyor-type dryer, excessive drying is required to suppress the generation of undried matter. When excessive drying is performed, a large amount of high-temperature gas is required, the amount of energy used during drying is large, and there are technical problems such as reduced absorption performance of the obtained water-absorbent resin composition and the generation of colored foreign matter.

[0006] In addition, as a method of drying the water-absorbent resin composition other than using a conveyor dryer, a method of drying by suspending a hydrogel using an air flow (Patent Document 3) and a method of drying using a rotary dryer (Patent Documents 4 and 5) have been proposed.

[0007] However, since the hydrogel has high cohesiveness, the hydrogel aggregates and its fluidity decreases, and it adheres to the dryer and remains in the dryer, so that a part of the hydrogel is overheated and the water absorption performance deteriorates, and colored foreign matter is generated in the methods of Patent Documents 3 and 4. In addition, when the drying temperature is lowered to avoid thermal degradation, the production per unit time decreases due to the decrease in the drying speed, and the continuous operation of the equipment becomes difficult due to the adhesion of the undried gel to the dryer.

[0008] In order to improve the drying property, a method of adding a surfactant to a hydrogel for drying has been proposed (Patent Document 6). However, in a dryer with low drying efficiency, a large amount of surfactant material needs to be added, and there are problems such as coloration due to thermal degradation of the surfactant and deterioration of water absorption performance due to the addition of the surfactant.

[0009] As a measure to reduce colored foreign matter contained in a water-absorbent resin composition, a method of removing foreign matter by color sorting has been proposed (Patent Document 7). However, it is difficult to suppress deterioration of water absorption performance and the production process becomes complicated.

[0010] Prior art literature Patent Literature Patent Document 1: Japanese Patent No. 3297192 Patent Document 2: Japanese Patent No. 5587384 Patent Document 3: Japanese Patent Application Laid-Open No. 2007-71415 Patent Document 4: Japanese Patent No. 6913107 Patent Document 5: International Patent No. WO2020 / 144948 Patent Document 6: Japanese Patent Application Laid-Open No. 2000-143720 Patent Document 7: Japanese Patent Application Laid-Open No. 5271717 Summary of the invention Technical problem to be solved by the invention An object of the present invention is to provide a method for producing a water-absorbent resin composition, which can contribute to reducing environmental load by reducing the time required for a drying process, and can reduce performance degradation and generation of colored foreign matter caused by the drying process.

[0011] Technical solutions for solving technical problems The present invention is a method for producing a water-absorbent resin composition, comprising: a polymerization step of obtaining a hydrogel containing a crosslinked polymer (A), wherein the crosslinked polymer (A) has a monomer (A1) and an internal crosslinking agent (b) as structural units, wherein the monomer (A1) is one or more selected from a water-soluble unsaturated monocarboxylic acid (a1) and a salt thereof, and a monomer (a2) capable of becoming the water-soluble unsaturated monocarboxylic acid (a1) by hydrolysis; and a drying step of drying the hydrogel using a dryer. The dryer is a rotary dryer having a rotating drum rotatable about an axis and a rotatable stirring shaft arranged in the axis direction and having a stirring rod, and performing drying treatment in the rotating drum. In the drying step, the rotary drum and the stirring rod are rotated to dry the hydrogel in the rotary drum of the rotary dryer while stirring it up.

[0012] Effects of the Invention According to the present invention, it is possible to provide a method for producing a water-absorbent resin composition which can contribute to reducing environmental load by reducing the time required for a drying process and can reduce performance degradation and generation of colored foreign matter caused by the drying process. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a diagram schematically showing a part of a cross section of a rotary drum of a rotary dryer in the axial direction.

[0014] Figure 2 This is a diagram schematically showing a cross section in a direction perpendicular to the axis of a rotary drum of a rotary dryer.

[0015] Figure 3 This is a diagram schematically showing a cross section of a conventionally used conveyor type dryer. DETAILED DESCRIPTION

[0016] <Method for producing water-absorbent resin composition> The method for producing a water-absorbent resin composition according to the present embodiment is characterized by comprising: A polymerization step, wherein a hydrogel comprising a cross-linked polymer (A) is obtained, wherein the cross-linked polymer (A) has a monomer (A1) and an internal cross-linking agent (b) as structural units, wherein the monomer (A1) is at least one selected from a water-soluble unsaturated monocarboxylic acid (a1) and a salt thereof, and a monomer (a2) capable of becoming the water-soluble unsaturated monocarboxylic acid (a1) by hydrolysis; and a drying step, wherein the hydrogel is dried using a dryer, The dryer is a rotary dryer having a rotating drum rotatable about an axis and a rotatable stirring shaft arranged in the axis direction and having a stirring rod, and performing drying treatment in the rotating drum. In the drying step, the rotary drum and the stirring rod are rotated to dry the hydrogel while stirring it up in the rotary drum of the rotary dryer.

[0017] According to the method for producing a water-absorbent resin composition of the present embodiment, it is possible to contribute to reducing environmental load by reducing the time required for the drying process, and it is possible to reduce performance degradation and generation of colored foreign matter caused by the drying process.

[0018] 〔Polymerization process〕 The method for producing a water-absorbent resin composition according to the present embodiment comprises a polymerization step of obtaining a hydrogel including a crosslinked polymer (A), wherein the crosslinked polymer (A) has, as structural units, one or more monomers (A1) selected from a water-soluble unsaturated monocarboxylic acid (a1) and a salt thereof, and a monomer (a2) capable of becoming the water-soluble unsaturated monocarboxylic acid (a1) by hydrolysis, and an internal crosslinking agent (b). In the polymerization step, the hydrogel can be obtained by polymerizing a monomer composition including the monomer (A1) and the crosslinking agent (b).

[0019] [Monomer (A1)] (Water-soluble unsaturated monocarboxylic acid (a1) and its salt) The water-soluble unsaturated monocarboxylic acid (a1) can be used without particular limitation as long as it is water-soluble. From the viewpoint of water absorption performance when a cross-linked body is prepared and ease of obtaining, the water-soluble unsaturated monocarboxylic acid (a1) is preferably at least one selected from acrylic acid, methacrylic acid and crotonic acid, and more preferably acrylic acid or methacrylic acid.

[0020] Examples of the salt of the water-soluble unsaturated monocarboxylic acid (a1) include alkali metal (lithium, sodium, potassium, etc.) salts, alkaline earth metal (magnesium, calcium, etc.) salts, and ammonium (NH4) salts. Among these salts, alkali metal salts and ammonium salts are preferred from the viewpoint of absorption performance, etc., alkali metal salts are more preferred, and sodium salts are particularly preferred.

[0021] (Monomer (a2)) A monomer (a2) that can be converted into the water-soluble unsaturated monocarboxylic acid (a1) by hydrolysis can be used together with the water-soluble unsaturated monocarboxylic acid (a1) or can be used instead of the water-soluble unsaturated monocarboxylic acid (a1). The monomer (a2) is not particularly limited, and examples thereof include monomers having one hydrolyzable substituent that can be converted into a carboxyl group by hydrolysis. Examples of the hydrolyzable substituent include groups containing anhydride (1,3-oxo-1-oxapropylene, -COO-CO-), groups containing ester bonds (alkyloxycarbonyl, vinyloxycarbonyl, allyloxycarbonyl or propenyloxycarbonyl, -COOR), and cyano groups. It should be noted that R is an alkyl group having 1 to 3 carbon atoms (methyl, ethyl, and propyl), a vinyl group, an allyl group, and a propenyl group.

[0022] In this specification, water-soluble means that at least 100 g of the monomer is soluble in 100 g of water at 25° C. In addition, hydrolyzability in the monomer (a2) means the property of being hydrolyzed by water and a catalyst (acid or base, etc.) as required to become water-soluble. The hydrolysis of the monomer (a2) may be performed during polymerization, after polymerization, or both. From the viewpoint of the absorption performance of the obtained water-absorbent resin composition, it is preferably performed after polymerization.

[0023] The monomer composition may contain, in addition to the monomer (A1), another vinyl monomer (A2) copolymerizable with the monomer (A1). The vinyl monomer (A2) may be used alone or in combination of two or more.

[0024] The vinyl monomer (A2) is not particularly limited, and a known hydrophobic vinyl monomer (for example, the hydrophobic vinyl monomer disclosed in paragraphs 0028 to 0029 of Japanese Patent No. 3648553, the vinyl monomer disclosed in paragraph 0025 of Japanese Unexamined Patent Publication No. 2003-165883 and paragraph 0058 of Japanese Unexamined Patent Publication No. 2005-75982) can be used. Specifically, for example, the following vinyl monomers (i) to (iii) can be used.

[0025] (i) Aromatic ethylenic monomers having 8 to 30 carbon atoms Styrene, α-methylstyrene, vinyltoluene, hydroxystyrene and other styrenes, vinylnaphthalene, halogen-substituted styrenes such as dichlorostyrene and the like, and the like.

[0026] (ii) Aliphatic ethylenic monomers having 2 to 20 carbon atoms Olefins (ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene and octadecene, etc.); and dienes (butadiene and isoprene, etc.), etc.

[0027] (iii) Alicyclic ethylenic monomers having 5 to 15 carbon atoms Monoethylenically unsaturated monomers (pinene, limonene and indene, etc.); and polyethylene vinyl monomers [cyclopentadiene, dicyclopentadiene and ethylidene norbornene, etc.], etc.

[0028] From the viewpoint of absorption performance, etc., the amount of the vinyl monomer (A2) in the monomer composition is preferably 0 to 5 mol parts, more preferably 0 to 3 mol parts, particularly preferably 0 to 2 mol parts, and particularly preferably 0 to 1.5 mol parts, relative to 100 mol parts of the monomer (A1). From the viewpoint of absorption performance, etc., 0 mol part is most preferred.

[0029] [Internal crosslinking agent (b)] The internal crosslinking agent (b) is not particularly limited, and known crosslinking agents can be used (for example, a crosslinking agent having two or more ethylenically unsaturated groups, a crosslinking agent having at least one functional group capable of reacting with a water-soluble substituent and having at least one ethylenically unsaturated group, and a crosslinking agent having at least two functional groups capable of reacting with a water-soluble substituent disclosed in paragraphs 0031 to 0034 of Japanese Patent No. 3648553; Japanese Patent Laid-Open No. 2003-165883; The crosslinking agents disclosed in paragraphs 0028 to 0031 of the gazette have two or more ethylenically unsaturated groups, the crosslinking agents having an ethylenically unsaturated group and a reactive functional group, and the crosslinking agents having two or more reactive substituents; the crosslinkable vinyl monomer disclosed in paragraph 0059 of Japanese Patent Publication No. 2005-75982; and the crosslinkable vinyl monomer disclosed in paragraphs 0015 to 0016 of Japanese Patent Publication No. 2005-95759).

[0030] The internal crosslinking agent (b) is preferably a crosslinking agent having two or more ethylenically unsaturated groups. From the viewpoint of reactivity with the monomer and water absorption characteristics, poly (meth)allyl compounds and acrylamide compounds having two or more ethylenically unsaturated groups are preferred. More preferably, one or more selected from poly (meth)allyl ethers of polyols such as alkylene glycol, trimethylolpropane, glycerol, pentaerythritol and sorbitol, poly (meth)allyl compounds such as tetraallyloxyethane and triallyl isocyanurate, and poly (meth)acrylamide compounds having two or more (meth)acrylamide groups in one molecule are preferred. The internal crosslinking agent (b) may be used alone or in combination of two or more. From the viewpoint of reactivity and the balance between water retention and absorption under load, poly (meth)allyl ethers of polyols and poly (meth)acrylamide compounds are further preferably used.

[0031] From the viewpoint of absorption performance, etc., when 100 mol parts of the above-mentioned monomer (A1) and other vinyl monomer (A2) are used, the amount of the above-mentioned internal crosslinking agent (b) in the above-mentioned monomer composition is preferably 0.001 to 5 mol parts, more preferably 0.005 to 3 mol parts, and particularly preferably 0.005 to 1 mol part relative to 100 mol parts in total of (A1) and (A2).

[0032] When aqueous solution polymerization is performed, a mixed solvent containing water and an organic solvent may be used. Examples of the organic solvent include methanol, ethanol, acetone, methyl ethyl ketone, N,N-dimethylformamide, dimethyl sulfoxide, and a mixture of two or more thereof.

[0033] When aqueous solution polymerization is performed, the amount (weight %) of the organic solvent used is preferably 40 or less, more preferably 30 or less, based on the weight of water.

[0034] When the polymerization method is suspension polymerization or reversed phase suspension polymerization, polymerization can be carried out in the presence of a conventionally known dispersant or surfactant as required. In addition, in the case of reversed phase suspension polymerization, polymerization can be carried out using conventionally known hydrocarbon solvents such as xylene, n-hexane and n-heptane.

[0035] Among the polymerization methods, aqueous solution polymerization is preferred because it does not require the use of organic solvents and is advantageous in terms of production cost. Aqueous solution adiabatic polymerization is further preferred because it can produce an aqueous liquid absorbent resin with a large water retention capacity and a small amount of water-soluble components and does not require temperature control during polymerization.

[0036] The weight percentage concentration of the monomer composition containing the monomer (A1) and the internal crosslinking agent (b) during polymerization is preferably 15 to 55% relative to the total weight of the polymerization solution at the start of polymerization. If it is lower than this range, productivity may be poor, and if it is higher than this range, sufficient gel strength may not be obtained.

[0037] In the polymerization of the monomer (A1), a known radical initiator may be used as necessary.

[0038] Examples of known free radical initiators include azo compounds [azobisisobutyronitrile, azobiscyanovaleric acid, 2,2'-azobis(2-amidinopropane) hydrochloride, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], etc.], inorganic peroxides (hydrogen peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, etc.), organic peroxides [benzoyl peroxide, di-tert-butyl peroxide, cumene hydroperoxide, succinic acid peroxide, and di(2-hydroxyethyl)propionamide, etc.] -ethoxyethyl) peroxydicarbonate, etc.], redox catalyst (combination of reducing agents such as alkali metal sulfites or bisulfites, ammonium sulfite, ammonium bisulfite and ascorbic acid and oxidizing agents such as alkali metal persulfates, ammonium persulfate, hydrogen peroxide and organic peroxides), photo radical generators [2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, 1-hydroxycyclohexyl-phenyl ketone-hydroxyalkyl phenone, α-aminoalkyl phenone, etc.], etc. These radical initiators may be used alone or in combination of two or more thereof.

[0039] The amount of the radical initiator used is preferably 0.0005 to 5 parts by mole, more preferably 0.001 to 2 parts by mole, based on 100 parts by mole of the monomer (A1).

[0040] Through the above polymerization step, a polymer gel of a crosslinked polymer (A) having the above monomer (A1) and the above internal crosslinking agent (b) as structural units can be obtained, and the polymer gel can be chopped as needed. The size (longest diameter) of the chopped gel is preferably 50 μm to 10 cm, more preferably 100 μm to 2 cm, and particularly preferably 1 mm to 1 cm. In this range, the drying property in the drying step becomes better.

[0041] The above-mentioned hydrogel can be pulverized by a known method, and pulverization can be performed using a pulverizing device (for example, a Bexmill, a rubber cutter, a Pharmamill, a meat chopper, an impact mill, and a roller mill). In addition, a base can be mixed with the polymer gel obtained as described above to neutralize it as needed.

[0042] As the alkali, known alkalis {such as Japanese Patent Gazette No. 3205168} can be used. Among them, lithium hydroxide, sodium hydroxide and potassium hydroxide are preferred from the viewpoint of water absorption performance, sodium hydroxide and potassium hydroxide are further preferred, and sodium hydroxide is particularly preferred. From the viewpoint of water absorption performance and operability, the neutralization rate is preferably 20 to 100 mol%, and more preferably 50 to 80 mol%. When the degree of neutralization is less than 50 mol%, the adhesiveness of the obtained hydrogel polymer becomes high, and sometimes the operability during manufacture and use becomes poor. Furthermore, the water retention capacity of the obtained water-absorbing resin is sometimes reduced. On the other hand, when the degree of neutralization exceeds 80%, the pH of the obtained resin becomes high, and sometimes there are concerns about the safety of the human skin.

[0043] [Hydrophobic substance adding process] The method for producing the water-absorbent resin composition may include a hydrophobic substance adding step of adding a hydrophobic substance (c) before the drying step. The hydrophobic substance (c) can inhibit the adhesion caused by the aggregation of the hydrogel particles obtained by shredding the hydrogel, and the hydrogel particles are prevented from fusing with each other, thereby increasing the surface area of ​​the hydrogel during drying, thereby improving the drying property. In addition, the hydrogel can be prevented from adhering to the inside of the dryer, and the deterioration of the water absorption performance and the generation of colored foreign matter can be inhibited.

[0044] Examples of the hydrophobic substance (c) include a hydrophobic substance (c1) containing a hydrocarbon group having 8 to 30 carbon atoms and a hydrophobic substance (c2) which is an organopolysiloxane.

[0045] The hydrophobic substance (c1) includes polyolefin resins, polyolefin resin derivatives, polystyrene resins, polystyrene resin derivatives, waxes, long-chain fatty acid esters, long-chain fatty acids and salts thereof, long-chain aliphatic alcohols, long-chain aliphatic amides, and mixtures of two or more thereof.

[0046] Examples of the polyolefin resin include polymers having a weight average molecular weight of 1,000 to 1,000,000 {e.g., polyethylene, polypropylene, polyisobutylene, poly(ethylene-isobutylene) and isoprene} formed by using an olefin having 2 to 4 carbon atoms {ethylene, propylene, isobutylene and isoprene, etc.} as an essential constituent monomer (the content of the olefin is at least 50% by weight based on the weight of the polyolefin resin).

[0047] As polyolefin resin derivatives, polymers having a weight average molecular weight of 1,000 to 1,000,000 in which a carboxyl group (-COOH), 1,3-oxo-2-oxapropylene (-COOCO-), etc. are introduced into the polyolefin resin can be cited {for example, polyethylene thermal degradation products (Japanese: 熱減成体), polypropylene thermal degradation products, maleic acid-modified polyethylene, chlorinated polyethylene, maleic acid-modified polypropylene, ethylene-acrylic acid copolymer, ethylene-maleic anhydride copolymer, isobutylene-maleic anhydride copolymer, maleated polybutadiene, ethylene-vinyl acetate copolymer, and maleated products of ethylene-vinyl acetate copolymer, etc.}.

[0048] As polystyrene resin, polymers having a weight average molecular weight of 1,000 to 1,000,000, etc. can be used.

[0049] As polystyrene resin derivatives, polymers having a weight average molecular weight of 1,000 to 1,000,000 in which styrene is a necessary constituent monomer (the content of styrene is at least 50% by weight based on the weight of the polystyrene derivative) can be cited {for example, styrene-maleic anhydride copolymer, styrene-butadiene copolymer, styrene-isobutylene copolymer, etc.}.

[0050] As waxes, waxes having a melting point of 50 to 200 °C can be cited {for example, paraffin wax, beeswax, carnauba wax, beef tallow, etc.}.

[0051] As long-chain fatty acid esters, esters of fatty acids having 8 to 30 carbon atoms and alcohols having 1 to 12 carbon atoms can be cited {for example, methyl laurate, ethyl laurate, methyl stearate, ethyl stearate, methyl oleate, ethyl oleate, monolaurin, monostearin, monoolein, monolaureate of pentaerythritol, monostearate of pentaerythritol, monooleate of pentaerythritol, monolaurate of sorbitol, monostearate of sorbitol, monooleate of sorbitol, monopalmitate of sucrose, dipalmitate of sucrose, tripalmitate of sucrose, monostearate of sucrose, distearate of sucrose, tristearate of sucrose, and beef tallow, etc.}.

[0052] As long-chain fatty acids and their salts, fatty acids having 8 to 30 carbon atoms can be cited {for example, lauric acid, palmitic acid, stearic acid, oleic acid, dimer acid, behenic acid, etc.}, and as their salts, salts with zinc, calcium, magnesium, or aluminum (hereinafter simply referred to as Zn, Ca, Mg, Al, respectively) can be cited {for example, Ca palmitate, Al palmitate, Ca stearate, Mg stearate, Al stearate, etc.}.

[0053] As long-chain aliphatic alcohols, aliphatic alcohols having 8 to 30 carbon atoms can be cited {for example, lauryl alcohol, palmityl alcohol, stearyl alcohol, oleyl alcohol, etc.}. From the viewpoint of the leakage resistance of the absorbent article, etc., palmityl alcohol, stearyl alcohol, and oleyl alcohol are preferred, and stearyl alcohol is more preferred.

[0054] Examples of the long-chain aliphatic amide include amidates of a long-chain aliphatic primary amine having 8 to 30 carbon atoms and a carboxylic acid having a hydrocarbon group having 1 to 30 carbon atoms, amidates of ammonia or a primary amine having 1 to 7 carbon atoms and a long-chain fatty acid having 8 to 30 carbon atoms, amidates of a long-chain aliphatic secondary amine having at least one aliphatic chain having 8 to 30 carbon atoms and a carboxylic acid having 1 to 30 carbon atoms, and amidates of a secondary amine having two aliphatic hydrocarbon groups having 1 to 7 carbon atoms and a long-chain fatty acid having 8 to 30 carbon atoms.

[0055] The amidates of a long-chain aliphatic primary amine having 8 to 30 carbon atoms and a carboxylic acid having a hydrocarbon group having 1 to 30 carbon atoms can be divided into an amidate formed by a 1:1 reaction between the primary amine and the carboxylic acid and an amidate formed by a 1:2 reaction. Examples of the amidate formed by a 1:1 reaction include acetic acid N-octylamide, acetic acid N-cosylamide, heptacosanoic acid N-octylamide, and heptacosanoic acid N-cosylamide. Examples of the amidate formed by a 1:2 reaction include diacetic acid N-octylamide, diacetic acid N-cosylamide, di(heptacosanoic acid) N-octylamide, and di(heptacosanoic acid) N-cosylamide. It should be noted that in the case of an amidate formed by a 1:2 reaction between a primary amine and a carboxylic acid, the carboxylic acids used may be the same or different.

[0056] The amidates of ammonia or a primary amine having 1 to 7 carbon atoms and a long-chain fatty acid having 8 to 30 carbon atoms can be divided into an amidate formed by a 1:1 reaction of ammonia or a primary amine and a carboxylic acid and an amidate formed by a 1:2 reaction. Examples of the amidate formed by a 1:1 reaction include nonanoic acid amide, nonanoic acid methyl amide, nonanoic acid N-heptyl amide, heptacosanoic acid amide, heptacosanoic acid N-methyl amide, heptacosanoic acid N-heptyl amide, and heptacosanoic acid N-hexacosanoic acid amide. Examples of the amidate formed by a 1:2 reaction include dinonanoic acid amide, dinonanoic acid N-methyl amide, dinonanoic acid N-heptyl amide, dioctadecanoic acid amide, dioctadecanoic acid N-ethyl amide, dioctadecanoic acid N-heptyl amide, diheptacosanoic acid amide, diheptacosanoic acid N-methyl amide, diheptacosanoic acid N-heptyl amide, and diheptacosanoic acid N-hexacosanoic acid amide. In addition, as the amidate formed by reacting ammonia or a primary amine with a carboxylic acid at a ratio of 1:2, the carboxylic acids used may be the same or different.

[0057] Examples of the amidates of a long-chain aliphatic secondary amine having at least one aliphatic chain having 8 to 30 carbon atoms and a carboxylic acid having 1 to 30 carbon atoms include acetic acid N-methyloctylamide, acetic acid N-methylhexacosylamide, acetic acid N-octylhexacosylamide, acetic acid N-di(hexacosyl)amide, acetic acid N-methyloctylamide, heptacosanoic acid N-methylhexacosylamide, heptacosanoic acid N-octylhexacosylamide and heptacosanoic acid N-di(hexacosyl)amide.

[0058] Examples of the amidates of a secondary amine having two aliphatic hydrocarbon groups having 1 to 7 carbon atoms and a long-chain fatty acid having 8 to 30 carbon atoms include nonanoic acid N-dimethylamide, nonanoic acid N-methylheptylamide, nonanoic acid N-diheptylamide, heptacosanoic acid N-dimethylamide, heptacosanoic acid N-methylheptylamide and heptacosanoic acid N-diheptylamide.

[0059] Examples of the hydrophobic substance (c2) include polydimethylsiloxane, polyether-modified polysiloxane {polyoxyethylene-modified polysiloxane and poly(oxyethylene·oxypropylene)-modified polysiloxane, etc.}, carboxyl-modified polysiloxane, epoxy-modified polysiloxane, amino-modified polysiloxane, alkoxy-modified polysiloxane, and mixtures thereof.

[0060] The HLB value of the hydrophobic substance (c) is preferably 1 to 10, more preferably 2 to 8, and particularly preferably 3 to 7. In this range, the anti-blocking property during initial swelling becomes better. It should be noted that the HLB value refers to the hydrophilicity-hydrophobicity balance (HLB) value, which is obtained by the Oda method (New Introduction to Surfactants, page 197, Takehiko Fujimoto, published by Sanyo Chemical Industries, Ltd., published in 1981).

[0061] Among the above-mentioned hydrophobic substances (c), from the viewpoint of anti-blocking property during initial swelling, the above-mentioned hydrophobic substance (c1) is preferred, long-chain fatty acid esters, long-chain fatty acids and salts thereof, long-chain aliphatic alcohols, and long-chain aliphatic amides are more preferred, sorbitan stearate, sucrose stearate, stearic acid, Mg stearate, Ca stearate, Zn stearate, and Al stearate are further preferred, sucrose stearate and Mg stearate are particularly preferred, and sucrose stearate is most preferred.

[0062] From the viewpoint of absorption performance and anti-blocking property during initial swelling, the amount of the hydrophobic substance (c) is preferably 0.001 to 1.0 part by weight, more preferably 0.005 to 0.5 part by weight, and particularly preferably 0.01 to 0.3 part by weight, based on 100 parts by weight of the cross-linked polymer (A).

[0063] 〔Drying process〕 The method for producing a water-absorbent resin composition of the present embodiment comprises a drying step of drying the hydrogel using a dryer. The dryer is a rotary dryer having a rotating drum rotatable about an axis and a rotatable stirring shaft disposed in the axis direction and having a stirring rod, and the drying process is performed in the rotating drum. The rotating drum and the stirring rod are rotated to dry the hydrogel while stirring it in the rotating drum of the rotary dryer.

[0064] In the drying step, the hydrogel is dried by heating the hydrogel in the rotating drum. The means for heating the hydrogel is not limited as long as it is a means capable of applying heat required for drying, and examples thereof include heating means utilizing convection heat transfer, conduction heat transfer, microwaves, infrared rays, etc., and heating utilizing convection heat transfer is preferred from the viewpoint of drying efficiency.

[0065] As a drying method using convective heat transfer, there can be mentioned a method of introducing an airflow heated to a high temperature into a dryer. There is no limitation on the type of airflow, but air or nitrogen is preferred, and air is most preferred. There is no limitation on the temperature of the airflow, but hot air is preferred. From the viewpoints of drying efficiency, absorption performance, and coloring, the temperature (°C) of the airflow at the inlet of the dryer is preferably 200 to 500, more preferably 250 to 450, and most preferably 300 to 400. From the viewpoints of drying efficiency and coloring, the absolute humidity (kg / kg) of the hot air at the inlet of the dryer is preferably 0.001 to 1.0, more preferably 0.002 to 0.8, and most preferably 0.005 to 0.6. There is no particular limitation on the wind speed (m / s) of the airflow, but from the viewpoints of drying efficiency, absorption performance, and coloring, it is preferably 1 to 30, more preferably 1 to 20, and most preferably 1 to 10.

[0066] It is preferred that the moving direction of the hot air in the rotating drum is the same as the moving direction of the water-containing gel in the rotating drum.

[0067] An example of the above-mentioned rotary dryer used in the above-mentioned drying step will be described with reference to the drawings.

[0068] Figure 1 1 is a schematic structural diagram of the rotary dryer 100. The rotary dryer 100 has a rotary drum 1 that can rotate around an axis. Figure 1 In order to explain the interior of the rotating drum 1, a part of the rotating drum 1 in the axial direction is shown in a cross-sectional view.

[0069] The rotary dryer 100 has, at one end of the rotary drum 1, a hydrogel inlet 3 for inletting the hydrogel, and a hot air inlet 2 for inletting hot air above the hydrogel inlet 3 at the same end. The rotary dryer 100 has, at the other end of the rotary drum 1, a dry polymer outlet 8 for discharging a dry polymer obtained by drying the hydrogel inlet 3, and a hot air outlet 7 for discharging the hot air inlet 2 above the dry polymer outlet 8.

[0070] From the viewpoint of drying efficiency, the inner diameter (diameter) of the rotating drum 1 is preferably 0.5 to 5.0 m, more preferably 1.0 to 4.0 m, and most preferably 2.0 to 3.5 m. In addition, from the viewpoint of drying efficiency, the length of the rotating drum 1 in the axial direction (the long axis direction of the rotating drum 1) is preferably 1 to 20 m, more preferably 3 to 15 m, further preferably 5 to 12 m, and most preferably 6 to 10 m.

[0071] The rotating drum 1 has a lifter 4 on its inner wall for stirring the water-containing gel. A rotatable stirring shaft 6 is disposed inside the rotating drum 1 along the axial direction of the rotating drum 1. The stirring shaft 6 has a plurality of stirring rods 5 for stirring the water-containing gel.

[0072] Figure 2 1 is a diagram schematically showing a cross section in a direction perpendicular to the axis of the rotating drum 1. The lifting member 4 extends from the inner wall of the rotating drum 1 toward the axis of the rotating drum 1. In the drying step, the rotating drum 1 rotates in one direction around the axis to stir the water-containing gel by the lifting member 4, and the stirring shaft 6 rotates to stir the water-containing gel by the stirring rod 5. The rotation directions of the rotating drum 1 and the stirring shaft 6 are not particularly limited. For example, Figure 2 In the case where the rotating drum 1 rotates in the direction of the arrow indicated by the rotating drum rotation direction 10, the stirring shaft 6 rotates in the same direction as the rotating drum rotation direction 10, that is, the stirring shaft rotation direction 9. As the rotating drum 1 and the rotating shaft 6 rotate in the same direction, the hydrogel is broken by the lifting member 4 and the stirring rod 5, the contact efficiency between the hydrogel and the hot air is increased, and the drying efficiency is improved. In addition, when the hydrophobic substance (c) is added in the hydrophobic substance adding step, the breaking efficiency of the hydrogel is further improved, and the drying efficiency is further improved.

[0073] In the drying step, the water content of the hydrogel put into the rotating drum 1 is preferably 45 to 90%, more preferably 50 to 85%, and most preferably 60 to 80%. If the water content is high, the drying property is poor, causing problems in the generation of foreign matter and the subsequent drying process. On the other hand, when the water content is low, the absorption performance is poor. It should be noted that the water content can be measured by the method described in the examples.

[0074] The lifting member 4 extends from the inner wall of the rotating drum 1 toward the axial side of the rotating drum 1. The shape of the lifting member 4 is not particularly limited, and may be a flat lifting member, a U-shaped lifting member, or the like. From the viewpoints of stirring efficiency and drying performance, a flat lifting member and / or a U-shaped lifting member are preferred, and from the viewpoint of drying efficiency, a U-shaped lifting member is further preferred. It should be noted that a flat lifting member refers to a flat plate-shaped lifting member, and a U-shaped lifting member refers to a lifting member formed by bending a flat lifting member more than 0° and less than 90°. Figure 2 The lifting member 4 is a U-shaped lifting member. From the viewpoint of drying efficiency accompanied by stirring efficiency, the U-shaped lifting member is preferably bent forward by 10° to 60° in the rotation direction of the rotating drum 1.

[0075] In the drying step, from the viewpoint of drying efficiency, the rotation speed (rpm) of the stirring shaft 6 when drying the hydrogel is preferably 1 to 1000, more preferably 10 to 500, and particularly preferably 50 to 300.

[0076] In the drying step, the rotation speed (rpm) of the rotating drum 1 when drying the hydrogel is preferably 0.1 to 20, more preferably 0.5 to 15, and particularly preferably 1 to 10 from the viewpoint of drying efficiency.

[0077] The moisture content (wt%) of the water-containing gel after drying is preferably 0 to 20, more preferably 1 to 15, particularly preferably 2 to 13, and most preferably 3 to 12. Within this range, quality problems such as poor pulverization can be further reduced in the pulverization step described below.

[0078] 〔Crushing process〕 The method for producing the water-absorbent resin composition of the present embodiment may include a pulverizing step of pulverizing the water-absorbent resin composition obtained in the drying step to obtain a granular water-absorbent resin composition containing the cross-linked polymer (A).

[0079] In the pulverization step, the method for pulverizing the water-absorbent resin composition containing the cross-linked polymer (A) is not particularly limited, and a pulverizing device (e.g., a hammer mill, an impact mill, a roll mill, and a jet mill) etc. can be used. The particle size of the pulverized water-absorbent resin composition can be adjusted by sieving etc. as needed.

[0080] 〔Surface cross-linking process〕 The method for producing the water-absorbent resin composition of the present embodiment may include a surface crosslinking step of crosslinking the surface of the crosslinked polymer (A) with a surface crosslinking agent (d) after the polymerization step.

[0081] The water-absorbent resin composition obtained through the surface crosslinking step has a structure in which the surface of the crosslinked polymer (A) is crosslinked by the surface crosslinking agent (d). By crosslinking the surface of the crosslinked polymer (A), the gel strength of the water-absorbent resin composition can be improved, and the ideal water retention and absorption under load of the water-absorbent resin composition can be satisfied. In addition, the adhesion of the surface of the water-absorbent resin composition is suppressed, and uniform water absorption can be achieved, so that when decomposed with an oxidizing agent, it can also be expected that the decomposition efficiency can be improved.

[0082] The surface crosslinking agent (d) may be an inorganic substance or an organic substance. As the surface crosslinking agent (d), known organic surface crosslinking agents (such as polyglycidyl compounds, polyamines, polyaziridine compounds, and polyisocyanate compounds described in Japanese Patent Application Laid-Open No. 59-189103, polyols described in Japanese Patent Application Laid-Open No. 58-180233 and Japanese Patent Application Laid-Open No. 61-16903, silane coupling agents described in Japanese Patent Application Laid-Open No. 61-211305 and Japanese Patent Application Laid-Open No. 61-252212, alkylene carbonates described in Japanese Patent Application Laid-Open No. 5-508425, and polyoxazoline compounds described in Japanese Patent Application Laid-Open No. 11-240959) may be used. Among these surface crosslinking agents (d), polyglycidyl compounds, polyols and polyamines are preferred from the viewpoint of economic efficiency and absorption characteristics, polyglycidyl compounds and polyols are more preferred, polyglycidyl compounds are particularly preferred, and ethylene glycol diglycidyl ether is most preferred. The surface crosslinking agent (d) may be used alone or in combination of two or more.

[0083] The amount (wt%) of the surface crosslinking agent (d) used is not particularly limited because it can be varied depending on the type of the surface crosslinking agent, the conditions for crosslinking, the target performance, etc. However, from the viewpoint of absorption characteristics, etc., it is preferably 0.001 to 3, more preferably 0.005 to 2, and particularly preferably 0.01 to 1.5 based on the weight of the crosslinked polymer (A).

[0084] The surface crosslinking of the crosslinked polymer (A) can be carried out by mixing the crosslinked polymer (A) with the surface crosslinking agent (d) and heating. As a method for mixing the crosslinked polymer (A) and the surface crosslinking agent (d), there can be cited a method of uniformly mixing the crosslinked polymer (A) and the surface crosslinking agent (d) using the following mixing devices: a cylindrical mixer, a screw mixer, a screw extruder, a turbulence enhancer (Turbulizer), a Nauta mixer (NautaMixer), a double-arm kneader, a fluid mixer, a V-type mixer, a chopping mixer, a ribbon mixer, a fluid mixer, an airflow mixer, a rotating disk mixer, a cone mixer and a roller agitator. At this time, the surface crosslinking agent (d) can be used after being diluted with water and / or any solvent.

[0085] The temperature at which the cross-linked polymer (A) and the surface cross-linking agent (d) are mixed is not particularly limited, but is preferably 10 to 150°C, more preferably 20 to 100°C, and particularly preferably 25 to 80°C.

[0086] After the cross-linked polymer (A) and the surface cross-linking agent (d) are mixed, a heat treatment is usually performed. From the viewpoint of the damage resistance of the water-absorbent resin composition, the heating temperature is preferably 100 to 180°C, more preferably 110 to 175°C, and particularly preferably 120 to 170°C. If the heating is below 180°C, indirect heating using steam can be performed, which is advantageous in terms of equipment. At a heating temperature below 100°C, the absorption performance may deteriorate. In addition, the heating time can be appropriately set according to the heating temperature. From the viewpoint of the absorption performance, it is preferably 5 to 60 minutes, and more preferably 10 to 40 minutes. The water-absorbent resin composition obtained by surface cross-linking can also be further surface cross-linked using a surface cross-linking agent of the same type or a different type as the surface cross-linking agent used initially.

[0087] After the surface of the cross-linked polymer (A) is cross-linked by the surface cross-linking agent (d), the particle size is adjusted by sieving as needed. The average particle size of the obtained particles is preferably 100 to 600 μm, and more preferably 200 to 500 μm. The content of fine particles is preferably small, and the content of particles below 100 μm is preferably 3% by weight or less, and the content of particles below 150 μm is more preferably 3% by weight or less.

[0088] <Water-absorbent resin composition> The water-absorbent resin composition of the present embodiment contains a cross-linked polymer (A) having, as structural units, one or more monomers (A1) selected from the group consisting of water-soluble unsaturated monocarboxylic acids (a1) and salts thereof, and monomers (a2) capable of becoming the water-soluble unsaturated monocarboxylic acids (a1) by hydrolysis, and an internal cross-linking agent (b), wherein the number of colored foreign matter contained in 200 g of the water-absorbent resin composition is 50 or less. The water-absorbent resin composition can be produced by the method for producing a water-absorbent resin composition.

[0089] From the viewpoint of absorption performance, etc., the amount of the vinyl monomer (A2) unit in the cross-linked polymer (A) is preferably 0 to 5 mol parts, more preferably 0 to 3 mol parts, particularly preferably 0 to 2 mol parts, and particularly preferably 0 to 1.5 mol parts, relative to 100 mol parts in total of the structural units of the water-soluble unsaturated monocarboxylic acid (a1) and the structural units of the salts thereof. From the viewpoint of absorption performance, etc., the content of the vinyl monomer (A2) unit is most preferably 0 mol part.

[0090] From the viewpoint of absorption performance, etc., when using 100 mol parts in total of the structural units of the water-soluble unsaturated monocarboxylic acid (a1) and the structural units of the salts thereof, and other vinyl monomers (A2), the amount of the internal crosslinking agent (b) in the crosslinked polymer (A) is preferably 0.001 to 5 mol parts, more preferably 0.005 to 3 mol parts, and particularly preferably 0.005 to 1 mol part, relative to 100 mol parts in total of the structural units of the water-soluble unsaturated monocarboxylic acid (a1) and the structural units of the salts thereof, and the structural units of the vinyl monomers (A2).

[0091] From the viewpoint of decomposition performance, the amount of the internal crosslinking agent other than the internal crosslinking agent (b) is preferably 0 to 50 parts by mole relative to 100 parts by mole of the internal crosslinking agent (b).

[0092] The water-absorbent resin composition may contain the hydrophobic substance (c). When the water-absorbent resin composition contains the hydrophobic substance (c), the content of the hydrophobic substance (c) in the solid content of the water-absorbent resin composition is preferably 0.001 to 1% by weight, more preferably 0.005 to 0.5% by weight, and particularly preferably 0.01 to 0.3% by weight, from the viewpoint of absorption performance and anti-blocking property during initial swelling. In the present specification, the solid content of the water-absorbent resin composition can be determined by the following formula using the water content measured by heating and drying 5 g of the water-absorbent resin composition at 150° C. for 15 minutes using an infrared moisture meter (manufactured by Kett Scientific Laboratory Co., Ltd., FD-230).

[0093] Solid content weight of water-absorbent resin composition (g) = weight of water-absorbent resin composition (g) × {100 - moisture content (%)} / 100 The water-absorbent resin composition may contain the organosilicon compound. When the water-absorbent resin composition contains the organosilicon compound, the content of the organosilicon compound in the solid content of the water-absorbent resin composition is preferably 0.0005 to 0.040% by weight, more preferably 0.010 to 0.030% by weight, and even more preferably 0.015 to 0.025% by weight, from the viewpoint of preventing adhesion to a production process device or a pipe between devices and preventing damage.

[0094] The water-absorbent resin composition may contain some other components such as residual solvent and residual crosslinking component within a range that does not impair its performance.

[0095] Other examples of the above-mentioned other components include preservatives, antifungal agents, antibacterial agents, ultraviolet absorbers, antioxidants, colorants, fragrances, deodorants, liquid permeability improvers, inorganic powders, and organic fibrous materials, etc. The amount thereof is usually 5% by weight or less based on the weight of the above-mentioned water-absorbent resin composition.

[0096] From the viewpoint of water absorption performance, the water absorbent resin composition preferably contains at least one typical element selected from iodine, tellurium, antimony and bismuth as the other component. When the water absorbent resin composition contains the typical element, from the viewpoint of water absorption performance, the content of the typical element in the solid content of the water absorbent resin composition is preferably 0.0005 to 0.1% by weight, more preferably 0.001 to 0.05% by weight.

[0097] The shape of the water-absorbent resin composition is not particularly limited, and examples thereof include amorphous crushed shapes, flaky shapes, pearly shapes, and rice grain shapes. Among these, amorphous crushed shapes are preferred from the viewpoint of good entanglement with fibrous materials in disposable diaper applications and no risk of falling off from the fibrous materials.

[0098] The water retention capacity (g / g) of the water-absorbent resin composition can be measured by the method described below, and from the viewpoint of absorption capacity, it is preferably 28 or more, more preferably 33 or more, and particularly preferably 35 or more. From the viewpoint of viscosity, the upper limit is preferably 60 or less, more preferably 55 or less, and particularly preferably 50 or less. The water retention capacity can be appropriately adjusted by the amount (weight %) of the internal crosslinking agent (b) and the surface crosslinking agent (d) used.

[0099] The soluble content (wt%) of the water-absorbent resin composition can be measured by the method described in the examples. From the viewpoint of liquid permeability and water absorption rate, it is preferably less than 20% relative to the water-absorbent resin composition, and more preferably less than 15%. If the soluble content exceeds 20%, the soluble content will dissolve during water absorption, causing gel adhesion, which has an adverse effect on the liquid permeability and water absorption rate, which is not preferred. In the present invention, the amount of soluble content can be reduced by adjusting the type and amount of the internal crosslinking agent and the water content of the surface crosslinking agent.

[0100] From the viewpoint of reducing the foreign body sensation in disposable diapers, sanitary napkins, and incontinence products, the number of colored foreign matter contained in 200 g of the water-absorbent resin composition is preferably 50 or less, more preferably 30 or less, and particularly preferably 20 or less. The number of colored foreign matter contained in 200 g of the water-absorbent resin composition can be measured by the method described in the Examples.

[0101] The absorption under load (g / g) of the water-absorbent resin composition can be measured by the method described below, and from the viewpoint of the absorption under load of the diaper, it is preferably 15 or more, more preferably 20 or more, and particularly preferably 25 or more. It is empirically known that the absorption under load and the water retention capacity are opposite to each other, and depending on the structure of the diaper, there are cases where a high water retention capacity is required and cases where the absorption under load is required.

[0102] <Absorber> The absorbent body can be obtained by using the water-absorbent resin composition. As the absorbent body, the water-absorbent resin composition can be used alone or together with other materials to form an absorbent body. As the other materials, fibrous materials and the like can be cited. The structure and manufacturing method of the absorbent body when used together with the fibrous materials are the same as the known structures and manufacturing methods (Japanese Patent Publication No. 2003-225565, Japanese Patent Publication No. 2006-131767, Japanese Patent Publication No. 2005-097569, etc.).

[0103] As the fibrous material, cellulosic fibers, organic synthetic fibers, and a mixture of cellulosic fibers and organic synthetic fibers are preferred.

[0104] Examples of the cellulosic fibers include natural fibers such as fluff pulp, and cellulosic chemical fibers such as viscose rayon, acetate, and cuprammonium fibers. The raw materials (coniferous trees and broadleaved trees, etc.), production methods (chemical pulp, semi-chemical pulp, mechanical pulp, CTMP, etc.), and bleaching methods of the cellulosic natural fibers are not particularly limited.

[0105] Examples of organic synthetic fibers include polypropylene fibers, polyethylene fibers, polyamide fibers, polyacrylonitrile fibers, polyester fibers, polyvinyl alcohol fibers, polyurethane fibers, and heat-fusible composite fibers (fibers obtained by combining at least two of the above fibers having different melting points into sheath-core type, eccentric-core type, parallel type, etc., fibers obtained by blending at least two of the above fibers, and fibers obtained by modifying the surface of the above fibers, etc.).

[0106] Among these fibrous materials, preferred are cellulose-based natural fibers, polypropylene-based fibers, polyethylene-based fibers, polyester-based fibers, thermally fusible composite fibers, and mixed fibers thereof. In terms of excellent shape retention of the obtained water-absorbing agent after water absorption, further preferred are fluff pulp, thermally fusible composite fibers, and mixed fibers thereof.

[0107] The length and thickness of the fibrous material are not particularly limited, and any material having a length of 1 to 200 mm and a thickness of 0.1 to 100 deniers can be preferably used. The shape is not particularly limited as long as it is fibrous, and examples thereof include a thin cylindrical shape, a split filament shape, a short fiber shape, a filament shape, and a mesh shape.

[0108] When the water-absorbent resin particles are used together with fibrous material to form an absorbent, the weight ratio of the water-absorbent resin particles to the fibers (weight of the water-absorbent resin particles / weight of the fibrous material) is preferably 40 / 60 to 90 / 10, more preferably 70 / 30 to 80 / 20.

[0109] <Absorbent articles> The absorbent resin composition can be used to obtain absorbent articles. Specifically, the absorbent body is used. As absorbent articles, it can be applied not only to sanitary products such as disposable diapers and sanitary napkins, but also to various uses such as anti-condensation agents, water-retaining agents for agriculture / horticulture, residual soil solidification materials, disaster sandbags, waste blood solidification agents, disposable heating products, cold-keeping agents, alkaline battery applications, cosmetics, pet diapers, cat litter applications, etc., for the absorption of various aqueous liquids, retention agents, gelling agents, etc. The manufacturing method of the absorbent article is the same as the known method (methods described in Japanese Patent Publication No. 2003-225565, Japanese Patent Publication No. 2006-131767, Japanese Patent Publication No. 2005-097569, etc.).

[0110] Example The present invention will be further described below by way of examples and comparative examples, but the present invention is not limited thereto. Hereinafter, unless otherwise specified, part means part by weight, and % means % by weight.

[0111] <Evaluation method> The water retention, the absorption under load and the absorption rate measured by the Vortex test method were measured by the following methods in a room at 25±2°C and a humidity of 50±10%. The temperature of the physiological saline used was adjusted to 25±2°C before use.

[0112] 〔Water content〕 Using an infrared moisture meter (for example, FD-230 manufactured by Kett Scientific Laboratory Co., Ltd.), 5 g of a measurement sample is heat-dried at 150° C. for 15 minutes, and the moisture content is calculated from the weight difference before and after drying.

[0113] [Weight ratio of particles having a particle size of 1.4 mm or more relative to the total weight of the dry powder] The weight ratio of particles with a particle size of 1.4 mm or more relative to the total weight of the dry powder is measured using a ro-tap test sieve shaker and a standard sieve (JIS Z8801-1: 2006) by the method described in the sixth edition of Perry's Chemical Engineer's Handbook (McGraw-Hill Book Company, 1984, page 21). That is, the JIS standard sieves are combined in the order of 4.0 mm, 1.4 mm, 0.5 mm and a tray from the top, and about 50 g of the measured particles are placed in the top sieve, and vibrated for 5 minutes using a ro-tap test sieve shaker. The weight of the measured particles on each sieve and tray is weighed, and the total is set to 100% by weight, and the weight fraction of the particles on each sieve is calculated. The total weight fraction of particles above 4.0 mm and above 1.4 mm is taken as the weight ratio of particles with a particle size of 1.4 mm or more.

[0114] [Method for measuring water retention relative to 0.9 wt % physiological saline] 1.00 g of the test sample was added to a tea bag (20 cm long, 10 cm wide) made of a nylon mesh with a mesh size of 63 μm (JIS Z8801-1:2006), and then immersed in 1000 ml of saline (salt concentration 0.9%) without stirring for 1 hour, and then lifted and hung for 15 minutes to remove water. Then, each tea bag was placed in a centrifuge, centrifuged at 150G for 90 seconds, and the remaining saline was removed. The weight (h1) including the tea bag was measured, and the water retention was calculated according to the following formula. It should be noted that the temperature of the saline and the measurement atmosphere used was 25°C ± 2°C.

[0115] Water retention (g / g) = (h1) - (h2) In addition, (h2) is the weight of the tea bag measured by the same operation as above without measuring the sample.

[0116] [Method for determination of soluble components] 100 g of 0.9 wt% saline solution was weighed in a 300 ml plastic container, 1.2 g of water-absorbent resin particles were added to the saline solution, the container was sealed with plastic wrap, and the stirrer was rotated and stirred at 500 rpm for 3 hours to prepare a soluble component extract solution in which the soluble components of the water-absorbent resin particles were extracted. Then, the soluble component extract solution was filtered using filter paper manufactured by ADVANTEC Toyo Co., Ltd. (product name: JIS P 3801, No. 2, thickness 0.26 mm, retention particle size 5 μm). Then, 20 g of the obtained filtrate was weighed and 30 g of ion exchange water was added to prepare a measurement solution.

[0117] First, a blank test solution prepared by adding 30 g of ion-exchanged water to 20 g of 0.9 wt % saline was titrated with an N / 50 KOH aqueous solution until the pH of the saline reached 10. Then, the titration amount of the N / 50 KOH aqueous solution required for the 0.9 wt % saline to reach a pH of 10 was obtained ([W KOH,b ]ml). Then, the N / 10 HCl aqueous solution was titrated until the pH of the saline solution reached 2.7. Then, the titration amount of the N / 10 HCl aqueous solution required for the pH of the 0.9 wt % saline solution to reach 2.7 was obtained ([W HCl,b ]ml).

[0118] Next, the same operation as the above titration operation is performed on the above measurement solution, and the titration amount of the N / 50 KOH aqueous solution required to obtain the pH of the measurement solution to be 10 ([W KOH,S ]ml) and the titration amount of N / 10 aqueous HCl solution required to make the pH of the measurement solution 2.7 ([W HCl,S ]ml) method.

[0119] For example, in the case of water-absorbent resin particles containing acrylic acid and its sodium salt, the amount of unneutralized acrylic acid n COOH for, n COOH (mol) = (W KOH,S -W KOH,b )×(1 / 50) / 1000×5 In addition, the total amount of acrylic acid n tot for, n tot (mol) = (W HCl,S -W HCl,b )×(1 / 10) / 1000×5 In addition, the amount of substance n that neutralizes acrylic acid COONa for, n COONa (mol) = n tot -nCOOH Furthermore, the weight of unneutralized acrylic acid m COOH for, m COOH (g) = n COOH ×72 In addition, the amount of neutralized acrylic acid m COONa for, m COONa (g) = n COONa ×94 Based on the above and the water content ([W H2O ] weight %), the soluble content of the water-absorbent resin particles can be calculated by the following calculation formula.

[0120] Soluble content (wt%) = {(m COOH +m COONa )×100} / {1.2×(100-W H2O )} [Amount of colored foreign matter in 200 g of water-absorbent resin composition] 200g of the weighed sample is put into a 0.5L SUS hopper, and 70g of the sample is fed per minute to the automatic powder inspection device (feed width 25mm) using a vibrating feeder, and the foreign matter content is measured by image processing. It should be noted that the automatic powder inspection device refers to a device that can perform image processing on the sample fed to the line through a CCD line sensor camera (2048 pixels) and reflected lighting parallel to the CCD line sensor camera and transmitted lighting arranged on the opposite side of the CCD line sensor camera. (256 levels of grayscale, scanning rate 75μs, detection level 65, lighting brightness 200~255) [Method for measuring absorption under load] 0.16 g of the sample sieved to 250 to 500 μm using a 30-mesh sieve and a 60-mesh sieve was weighed in a cylindrical plastic tube (inner diameter: 25 mm, height: 34 mm) with a nylon mesh of 63 μm (JIS Z8801-1: 2006) attached to the bottom. The cylindrical plastic tube was placed vertically, and the sample was adjusted to a substantially uniform thickness on the nylon mesh. A weight (weight: 210.6 g, outer diameter: 24.5 mm) was added to the sample. After measuring the weight (M1) of the entire cylindrical plastic tube, the cylindrical plastic tube containing the sample and the weight was placed vertically in a petri dish (diameter: 12 cm) filled with 60 ml of physiological saline (salt concentration 0.9%), immersed in the nylon mesh side as the lower surface, and left to stand for 60 minutes. After 60 minutes, the cylindrical plastic tube was lifted from the petri dish and tilted to collect the water attached to the bottom in one place. The water was dripped in the form of water droplets. After removing the excess water, the weight of the entire cylindrical plastic tube containing the test sample and the weight (M2) was measured, and the absorption under load was calculated by the following formula. It should be noted that the temperature of the physiological saline solution and the measurement atmosphere used was 25°C ± 2°C.

[0121] Absorption under load (g / g) = {(M2) - (M1)} / 0.16 <Example 1> 〔Polymerization process〕 300 parts of acrylic acid (manufactured by Mitsubishi Chemical Corporation), 0.975 parts of pentaerythritol triallyl ether (manufactured by DAISO Corporation) as a crosslinking agent (b) and 691 parts of deionized water were stirred and mixed to prepare a monomer aqueous solution, and the mixed solution was put into a polymerization tank capable of adiabatic polymerization. By introducing nitrogen gas into the solution, the amount of dissolved oxygen in the solution was set to 0.2 ppm or less, and the solution temperature was set to 5°C. In the polymerization solution, 4.5 parts of a 2% aqueous solution of 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 1.2 parts of a 1% aqueous solution of hydrogen peroxide and 2.25 parts of a 2% aqueous solution of ascorbic acid were added and mixed to initiate polymerization. After confirming that the temperature rise indicating the start of polymerization reached about 90°C, the mixture was further aged for 9 hours to obtain a water-containing gel polymer.

[0122] [Gel shredding process] While kneading and chopping the hydrogel obtained in the polymerization step with a chopper, 247 parts of a 48.5% sodium hydroxide aqueous solution was added and mixed, and the mixture was chopped three times with a chopper to obtain a chopped gel. Subsequently, 0.6 parts of an anti-gel blocking agent (c-1) {sucrose stearate} was added and mixed, and the mixture was further chopped once with a chopper to obtain hydrogel particles.

[0123] 〔Drying process〕 Use with Figure 1 and Figure 2The obtained hydrogel particles are dried in a rotary dryer with a stirring rod having the basic structure shown. The rotary drum of the rotary dryer has a U-shaped lifting piece on its inner wall. Hydrogel particles having a moisture content as shown in Table 1 and hot air at an absolute humidity of 0.15 kg / kg and 400°C are introduced from each inlet. The hydrogel particles are continuously dried with an average residence time of 20 minutes while the rotary drum is rotated at 5 rpm in the bending direction of the U-shaped lifting piece and the rotating shaft is rotated at 200 rpm in the same direction as the rotating direction of the rotary drum, thereby obtaining a dry powder (1) containing a cross-linked polymer (A).

[0124] Next, the dry powder (1) was pulverized with a roll mill (RM-10 roll mill, Asano Iron Works Co., Ltd.) at a gap of 0.35 mm, and then sieved to adjust the particle size to a mesh size range of 710 to 150 μm to obtain resin particles (A-1) containing a crosslinked polymer (A).

[0125] 〔Surface cross-linking process〕 Next, while 100 parts of the obtained resin particles (A-1) were subjected to high-speed stirring (high-speed stirring turbulence enhancer manufactured by Hosokawa Micron Co., Ltd.: rotation speed 2000 rpm), a mixed solution of 0.05 parts of ethylene glycol diglycidyl ether, 0.5 parts of propylene glycol and 1.7 parts of water as a surface crosslinking agent (d) was added, and after uniform mixing, the mixture was heated at 140° C. for 40 minutes to obtain a granular water-absorbent resin composition (P-1).

[0126] <Example 2> In Example 1, except having changed the introduction temperature of the hot air into 250 degreeC, it carried out similarly to Example 1, and obtained the water-absorbent resin composition (P-2).

[0127] <Example 3> In Example 1, except having changed the introduction temperature of the hot air into 450 degreeC, it carried out similarly to Example 1, and obtained the water-absorbent resin composition (P-2).

[0128] <Example 4> In Example 1, a water-absorbent resin composition (P-4) was obtained in the same manner as in Example 1 except that 0.6 parts of the hydrophobic substance (c-1) {sucrose stearate} was changed to 0.03 parts.

[0129] <Example 5> In Example 1, a water-absorbent resin composition (P-5) was obtained in the same manner as in Example 1 except that 0.6 parts of the hydrophobic substance (c-1) {sucrose stearate} was changed to 1.5 parts.

[0130] <Example 6> 〔Polymerization process〕 200 parts of acrylic acid (manufactured by Mitsubishi Chemical Corporation), 0.65 parts of pentaerythritol triallyl ether (manufactured by DAISO Corporation) as a crosslinking agent (b) and 794 parts of deionized water were stirred and mixed to prepare a monomer aqueous solution, and the mixed solution was put into a polymerization tank capable of adiabatic polymerization. By introducing nitrogen gas into the solution, the amount of dissolved oxygen in the solution was set to 0.2 ppm or less, and the solution temperature was set to 5°C. 3.0 parts of a 2% aqueous solution of 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 0.8 parts of a 1% aqueous solution of hydrogen peroxide and 1.50 parts of a 2% aqueous solution of ascorbic acid were added and mixed to initiate polymerization. After confirming that the temperature rise indicating the start of polymerization reached about 90°C, the mixture was further aged for 9 hours to obtain a water-containing gel polymer.

[0131] [Gel shredding process] While kneading and chopping the hydrogel obtained in the polymerization step with a chopper, 165 parts of a 48.5% sodium hydroxide aqueous solution was added and mixed, and the mixture was chopped three times with a chopper to obtain a chopped gel. Subsequently, 0.4 parts of a hydrophobic substance (c-1) {sucrose stearate} was added and mixed, and the mixture was further chopped once with a chopper to obtain hydrogel particles.

[0132] 〔Drying process〕 Use with Figure 1 and Figure 2 The obtained hydrogel particles are dried in a rotary dryer with a stirring rod having the basic structure shown. The rotary drum of the rotary dryer has a U-shaped lifting piece on its inner wall. Hydrogel particles having a moisture content as shown in Table 1 and hot air at an absolute humidity of 0.15 kg / kg and 400°C are introduced from each inlet. The hydrogel particles are continuously dried with an average residence time of 20 minutes while the rotary drum is rotated at 5 rpm in the bending direction of the U-shaped lifting piece and the rotating shaft is rotated at 200 rpm in the same direction as the rotating direction of the rotary drum, thereby obtaining a dry powder (2) containing a cross-linked polymer (A).

[0133] Next, the dry powder (2) was pulverized with a roll mill (RM-10 roll mill, Asano Iron Works Co., Ltd.) at a gap of 0.35 mm, and then sieved to adjust the particle size range to 710 to 150 μm, thereby obtaining resin particles (A-6) containing a crosslinked polymer (A).

[0134] 〔Surface cross-linking process〕 Next, while 100 parts of the resin particles (A-6) were being stirred at high speed (high-speed stirring turbulence enhancer manufactured by Hosokawa Micron Co., Ltd.: rotation speed 2000 rpm), a mixed solution of 0.05 parts of ethylene glycol diglycidyl ether, 0.5 parts of propylene glycol and 1.7 parts of water as a surface crosslinking agent (d) was added, and after being uniformly mixed, the mixture was heated at 140° C. for 40 minutes to obtain a granular water-absorbent resin composition (P-6).

[0135] <Example 7> 〔Polymerization process〕 To a solution (A) prepared by adding 0.975 parts of polyethylene glycol diacrylate (weight average molecular weight 523) (manufactured by TCI Corporation) as a crosslinking agent (b) to 300 parts of acrylic acid (manufactured by Mitsubishi Chemical), a solution (B) prepared by diluting 247 parts of a 48.5% sodium hydroxide aqueous solution with 444 parts of deionized water was mixed under stirring while controlling the temperature at not more than 40°C to prepare a mixed solution, which was then put into a polymerization tank. Nitrogen gas was introduced into the solution so that the amount of dissolved oxygen in the solution was 0.2 ppm or less, and the solution temperature was 10°C. To the polymerization solution, 4.5 parts of a 2% 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] aqueous solution, 1.20 parts of a 1% hydrogen peroxide aqueous solution, and 2.25 parts of a 2% ascorbic acid aqueous solution were added and mixed to initiate polymerization. The polymerization was carried out while removing heat, and after the temperature reached about 90°C and heat generation due to the reaction heat was no longer observed, the mixture was further aged for 9 hours to obtain a hydrogel polymer.

[0136] [Gel shredding process] The hydrogel obtained in the polymerization step was kneaded and chopped with a chopper, and chopped three times to obtain a chopped gel. Then, 0.6 parts of a hydrophobic substance (c-1) {sucrose stearate} was added and mixed, and further chopped once with a chopper to obtain hydrogel particles.

[0137] 〔Drying process〕 Use with Figure 1 and Figure 2 The obtained hydrogel particles are dried in a rotary dryer with a stirring rod having the basic structure shown. The rotary drum of the rotary dryer has a U-shaped lifting piece on its inner wall. Hydrogel particles having a moisture content as shown in Table 1 and hot air at an absolute humidity of 0.15 kg / kg and 400°C are introduced from each inlet. The hydrogel particles are continuously dried with an average residence time of 20 minutes while the rotary drum is rotated at 5 rpm in the bending direction of the U-shaped lifting piece and the rotating shaft is rotated at 200 rpm in the same direction as the rotating direction of the rotary drum, thereby obtaining a dry powder (3) containing a cross-linked polymer (A).

[0138] Next, the dry powder (3) was pulverized with a roll mill (RM-10 roll mill, Asano Iron Works Co., Ltd.) at a gap of 0.35 mm, and then sieved to adjust the particle size range to 710 to 150 μm, thereby obtaining resin particles (A-7) containing a crosslinked polymer (A).

[0139] 〔Surface cross-linking process〕 Next, while 100 parts of the resin particles (A-7) were being stirred at high speed (high-speed stirring turbulence enhancer manufactured by Hosokawa Micron Co., Ltd.: rotation speed 2000 rpm), a mixed solution of 0.05 parts of ethylene glycol diglycidyl ether, 0.5 parts of propylene glycol and 1.7 parts of water as a surface crosslinking agent (d) was added, and after being uniformly mixed, the mixture was heated at 140° C. for 40 minutes to obtain a granular water-absorbent resin composition (P-7).

[0140] <Example 8> 〔Polymerization process〕 To a solution (A) prepared by adding 1.3 parts of polyethylene glycol diacrylate (weight average molecular weight 523) (manufactured by TCI Corporation) as a crosslinking agent (b) to 400 parts of acrylic acid (manufactured by Mitsubishi Chemical), a solution (B) prepared by diluting 330 parts of a 48.5% sodium hydroxide aqueous solution with 258 parts of deionized water was mixed under ice cooling while stirring and controlling the temperature so as not to exceed 40°C to prepare a mixed solution, which was then put into a polymerization tank. Nitrogen gas was introduced into the solution so that the amount of dissolved oxygen in the solution was 0.2 ppm or less, and the solution temperature was 10°C. To the polymerization solution, 6.0 parts of a 2% 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] aqueous solution, 1.60 parts of a 1% hydrogen peroxide aqueous solution, and 3.00 parts of a 2% ascorbic acid aqueous solution were added and mixed to initiate polymerization. The polymerization was carried out while removing heat, and after the temperature reached about 90°C and heat generation due to the reaction heat was no longer observed, the mixture was further aged for 9 hours to obtain a hydrogel polymer.

[0141] [Gel shredding process] The hydrogel obtained in the polymerization step was kneaded and chopped with a chopper, and chopped three times to obtain a chopped gel. Then, 0.8 parts of a hydrophobic substance (c-1) {sucrose stearate} was added and mixed, and further chopped once with a chopper to obtain hydrogel particles.

[0142] 〔Drying process〕 Use with Figure 1 and Figure 2The obtained hydrogel particles are dried in a rotary dryer with a stirring rod having the basic structure shown. The rotary drum of the rotary dryer has a U-shaped lifting piece on its inner wall. Hydrogel particles having a moisture content as shown in Table 1 and hot air at an absolute humidity of 0.15 kg / kg and 400°C are introduced from each inlet. The hydrogel particles are continuously dried with an average residence time of 20 minutes while the rotary drum is rotated at 5 rpm in the bending direction of the U-shaped lifting piece and the rotating shaft is rotated at 200 rpm in the same direction as the rotating direction of the rotary drum, thereby obtaining a dry powder (4) containing a cross-linked polymer (A).

[0143] Next, the dry powder (4) was pulverized with a roll mill (RM-10 roll mill, Asano Iron Works Co., Ltd.) at a gap of 0.35 mm, and then sieved to adjust the particle size to a mesh size range of 710 to 150 μm to obtain resin particles (A-8) containing a crosslinked polymer.

[0144] (Surface cross-linking process) Next, while 100 parts of the resin particles (A-8) were being stirred at high speed (high-speed stirring turbulence enhancer manufactured by Hosokawa Micron Co., Ltd.: rotation speed 2000 rpm), a mixed solution of 0.05 parts of ethylene glycol diglycidyl ether, 0.5 parts of propylene glycol and 1.7 parts of water as a surface crosslinking agent (d) was added, and after being uniformly mixed, the mixture was heated at 140° C. for 40 minutes to obtain a granular water-absorbent resin composition (P-8).

[0145] <Comparative Example 1> In Example 1, a water-absorbent resin composition (R-1) was obtained in the same manner as in Example 1 except that a rotary dryer without a stirring rod was used.

[0146] <Comparative Example 2> In Example 1, a water-absorbent resin composition (R-2) was obtained in the same manner as in Example 1 except that the drying was performed without rotating the rotating drum and the stirring rod.

[0147] <Comparative Example 3> In Example 1, using Figure 3 A water-absorbent resin composition (R-3) was obtained in the same manner as in Example 1 except that the conveyor dryer exemplified in Example 1 was used.

[0148] The evaluation results of the water-absorbent resin compositions (P-1) to (P-8) and (R-1) to (R-3) are shown in Table 1 below.

[0149] [Table 1] From the results shown in Table 1, it can be seen that according to the method for producing a water-absorbent resin composition of the present invention, the moisture content after drying is low, troubles are less likely to occur in the pulverization step after the drying step, and the obtained water-absorbent resin composition has less colored foreign matter and excellent water absorption performance. It is presumed that this is because the thermal efficiency during drying in the production method of the present invention is high, and thermal degradation of the water-absorbent resin is suppressed.

[0150] Description of Reference Numerals 1 Rotating drum 2 Hot air inlet 3. Aqueous gel inlet 4 Lifting parts 5. Stirring stick 6. Stirring shaft 7 Hot air outlet 8 Dry polymer outlet 9 Stirring shaft rotation direction 10 Rotation direction of the rotating drum 11. Ventilation belt 12 Aqueous gel 13 Drying room 14 Ventilation direction 15 Movement direction of ventilation belt 16. Aqueous gel dried product.

Claims

1. A method for producing a water-absorbent resin composition, characterized in that: have: A polymerization step, wherein a hydrogel comprising a cross-linked polymer (A) is obtained, wherein the cross-linked polymer (A) has a monomer (A1) and an internal cross-linking agent (b) as structural units, wherein the monomer (A1) is at least one selected from a water-soluble unsaturated monocarboxylic acid (a1) and a salt thereof, and a monomer (a2) capable of becoming the water-soluble unsaturated monocarboxylic acid (a1) by hydrolysis; and a drying step, wherein the hydrogel is dried using a dryer, The dryer is a rotary dryer having a rotating drum rotatable about an axis and a rotatable stirring shaft disposed in the axis direction and having a stirring rod, and performing drying treatment in the rotating drum. In the drying step, the rotary drum and the stirring rod are rotated to dry the hydrogel while stirring it up in the rotary drum of the rotary dryer.

2. The method for producing a water-absorbent resin composition according to claim 1, wherein The rotary dryer has a lifting member extending from the inner wall of the rotary drum toward the axial center side of the rotary drum. In the drying step, the rotary drum is rotated to dry the hydrogel while stirring it up with the lifting member.

3. The method for producing a water-absorbent resin composition according to claim 2, wherein: The aqueous gel is stirred up by the lifting member, and the lifting member is selected from a flat lifting member and a U-shaped lifting member.

4. The method for producing a water-absorbent resin composition according to claim 1, wherein In the drying step, hot air is introduced into the rotating drum, and the water-containing gel is dried by convection heat transfer generated by the hot air.

5. The method for producing a water-absorbent resin composition according to claim 4, wherein When the hot air is supplied into the rotating drum, the supply temperature of the hot air is 200 to 500°C.

6. The method for producing a water-absorbent resin composition according to any one of claims 1 to 5, wherein: Prior to the drying step, a hydrophobic substance adding step of adding a hydrophobic substance (c) to the hydrogel is performed.

7. The method for producing a water-absorbent resin composition according to claim 6, wherein The hydrophobic substance (c) is a hydrophobic substance (c1) containing a hydrocarbon group having 8 to 30 carbon atoms and / or a hydrophobic substance (c2) being an organopolysiloxane.

8. The manufacturing method according to claim 6, wherein: The amount of the hydrophobic substance (c) is 0.001 to 1.0 part by weight based on 100 parts by weight of the cross-linked polymer (A).

Citation Information

Patent Citations

  • Deodorant sprayers

    JP1977071717A

  • Semiconductor memory circuit

    JP1980087384A

  • Absorbing agent

    JP1983180233A

  • Water-absorbing agent

    JP1984189103A

  • Water-absorbent

    JP1986016903A